Institutional framework for environmental management in Peru - Valdez Muñoz, Walter (2013)
The unfolding inclusion process of environmental management as a Government obligation is developed in this article, explaining its context and evolution in Latin America and the Caribbean plus the Peruvian case. The present document also sets some proposals, according to the author pointview, for improvement of the environmental institutional structure in Peru.